Breaking the silence on violation in South African prisons - Sandra Margaret Hoffman (Department of Psychology, 2024)
South Africa is legitimately recognized and admired internationally for changes it has made since 1994 from an authoritarian to a democratic political dispensation. While changes in visible forms of violation may have accompanied political change, its extent as a national crisis has been sustained. Invisible, underlying common patterns to violational forms remain testimony to the residues of the authoritarian ideology which plagued South Africa for decades. By locating violation within its socio-political and institutional contexts, I use lessons from the past as a starting block from which to introduce a theoretically sound radical paradigm shift. This intersubjective understanding requires suspension of traditional or moral-legal meaning structures in favour of one viewing violation as a matter of public health and safety. The voices of prisoners are seldom heard on the matter of violations. Ironically, in silencing them society may close itself off from its richest source of learning how to manage ( our own, and others') violations more effectively. My data is derived principally from 15 prisoners' voices in conversation with me, while I worked at a South African prison as a psychologist from 16 October 2000 to 31 November 2003. I follow a person-in-practice method, based largely on therapeutic relationships practised within the context of the institution in which they lived and I was employed. I adopt a critical approach both by introducing the notion of critical questioning in therapy, and when embedding case studies in socio-political and institutional contexts. Data has been interpreted from an intersubj ecti ve theoretical framework. This integration of methods flows from epistemological considerations which contrast strongly with more traditional views used in professional prison practice. The main findings of this research are, firstly that violations are an integral aspect of consciousness and evaluations of self, which are socially constructed. Violations are an indication of the struggle to survive a human quality of life and gain social recognition, in the face of predominant alienation. As such, they are intensely concerned with emotions. Secondly, violation is learned in childhood and becomes sustained as a way of life. It can realistically only change in crisis, through critical questioning, and in a non-judgmental environment. Change will only be sustained with practice. Thirdly, relationships in prison affect change or entrench violation in inmate, staff and institutional behaviour. In summary, while visible forms of violational behaviour differ, psychological dynamics of struggling for recognition and defending against alienation are universally shared between all of us.